KONDISI TERUMBU KARANG DI PULAU KARANG CONGKAK KEPULAUAN SERIBU - Santoso, Arif Dwi (Jurnal Hidrosfir Indonesia, 2010)
Seribu Island corral reef and reef fish are endangered by natural impact, various pressures from inland activities and destructive fishing practices. Cumulatively, these pressures appear to have significantly degraded corral reefs and its ecosystem over time. Meanwhile the corral reef ecosystem condition determines surroundings biodiversity condition that impact to local community. Therefore,it is necessary to serve and monitor corral reef ecosystem regularly. This article showed that corral reef covering at Karang Congkak Island was more lower abaout 27.41%. Degraded corral reefs occurred by several factors: increasing water temperature due to climate change, bathymetry and tide and destructive activity likely un-friendly fishing, corral mining and tourism activity.